Dekontruksi Sup Rogan Menjadi Panna Cotta - Fazua, Sabrina Alya; Zakiah, Siti (eProceedings of Applied Science, 2025)
This research is based on by the effort to preserve traditional cuisine thru deconstruction techniques, with a case study on transforming rogan soup, a traditional dish from Cianjur, West Java, made from a combination of white bread and young coconut, into a modern dessert, panna cotta. This dish is starting to be abandoned by the public due to a lack of recognition and also because of the soft texture of the bread, its liquid consistency, and its less-than-practical presentation, which has limited consumer acceptance of rogan soup. The focus of this research is to maintain the same flavor while offering a different texture and consumption experience. The research method used is a quantitative approach thru the formulation of a deconstructed recipe, adapting ingredients from rogan josh soup to panna cotta. Data collection involved 30 panelists in a hedonic test to assess consumer preferences, primarily regarding the organoleptic aspects of taste, texture, aroma, color, and appearance, to measure acceptance and evaluate improvements to the deconstructed product. Based on the test results, it can be indicated that positive responses are more dominant, especially in the appearance aspect, which received the highest percentage with 80.0% stating it is very attractive, 16.7% attractive, and 3.3% moderately attractive. The taste aspect received the lowest rating with a percentage of 56.70% stating it is very delicious, 36.7% delicious, and 6.7% moderately delicious. Keywords: rogan soup,bread, coconut, deconstruction, panna cotta.